Multi-approach provenance in stratigraphy: Implications for the Upper Mesozoic evolution of the Parnaiba Basin, NE Brazil - Cardoso, Alexandre Ribeiro; Rodrigues Nogueira, Afonso Cesar; Neri Rabelo, Cleber Eduardo; Soares, Joelson Lima; Goes, Ana Maria [UNESP] (Elsevier B.V., 2019)
Provenance analyses are highly affected by transport, depositional and diagenetic processes, as well as the grain size chosen for evaluation. In order to avoid misleading data, provenance research requires multi-approach techniques. In this work, a set of widespread methods were applied to investigate a debatable stratigraphic interval in the Parnaiba Basin, northeastern Brazil. Discontinuous exposures and fault displacements result in enigmatic stratigraphic relations in the Mesozoic portion of this basin. This succession consists of the lacustrine sandstones and shales of the Pastos Bons Formation and aeolian sandstones of the Corda Formation, composing the Mearim Group, and fluvial conglomerates and sandstones of the Grajad Formation. The provenance was studied through sandstone petrography, quartz petrography, hot cathodoluminescence and heavy minerals analyses. Sandstones from Mearim Group plotted in recycled orogenic and craton interior fields, whereas quartz petrography and cathodoluminescence constrained predominantly volcanic sources. The heavy minerals assemblages of the lacustrine and aeolian deposits are very similar, whereas the fluvial succession presents texturally immature grains and anomalous high hornblende content. Additionally, ZTR, GZi and RZi indexes are higher for lacustrine and aeolian deposits, and lower for fluvial beds. These data indicate polycyclic minerals and mixed sources for Mesozoic sandstones of the Parnaiba Basin. The Mearim Group presents both volcanic contribution, probably supplied by basalts from the Central Atlantic Magmatic Province (CAMP), and low to medium-grade metapelitic heavy minerals assemblage. Heavy minerals were probably supplied by Neoproterozoic metapelites from the Ceara Central Domain (Ceara Group?), Borborema Province. Conversely, heavy minerals of the Grajad Formation were derived from I-type Brazilian granites, incompatible with the Mearim Group. These data provided new stratigraphic relations for the Mesozoic deposits of the Parnaiba Basin and implications for the evolution of this basin.
Keywords: Provenance; Stratigraphic positioning; Heavy minerals; Cathodoluminescence; Parnaiba Basin